2019
DOI: 10.4028/www.scientific.net/kem.797.402
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Application of Palm Methyl Ester Sulfonate as an Interfacial Tension Reducing Surfactant for Chemical Enhanced Oil Recovery

Abstract: As the petroleum industry is facing challenges to add more oil reserves in their book, greater emphasis has been placed on improving the ultimate recovery factor for oilfields. When the recovery from primary and secondary methods could not be improved further, enhanced oil recovery (EOR) generally will be sought as the last option. One of the techniques applied in EOR is known as surfactant flooding. Though surfactants are very effective for the incremental oil recovery, there are implications during the post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Furtherore, palm oil based natural surfactant was used to reduce IFT in another research. And it was observed that IFT value reduced from 18 to 0.5 mN/m at the CMC about 0.1 wt.% . In another study, α-sodium ethel ester surfactant was synthesized from palm oil.…”
Section: Role Of Natural Surfactant In Eormentioning
confidence: 97%
See 2 more Smart Citations
“…Furtherore, palm oil based natural surfactant was used to reduce IFT in another research. And it was observed that IFT value reduced from 18 to 0.5 mN/m at the CMC about 0.1 wt.% . In another study, α-sodium ethel ester surfactant was synthesized from palm oil.…”
Section: Role Of Natural Surfactant In Eormentioning
confidence: 97%
“…( Sodium methyl ester sulfonate, ethyl ester sulfonate, alphasulfonated ethyl ester, and sodium-epoxidized MES (SEMES) can be considered as typical examples of this type of natural anionic surfactant; these are produced from the natural oil such as coconut oil, 76 jatropha oil, 77 mahua oil, 78 waste chicken fat, 79 and palm oil. 80 Other than sulfonate type, sulfate types are the other class of natural anionic surfactants as well. This kind of anionic surfactant has a high tolerance for salinity but a low tolerance for temperature.…”
Section: Classification Of Natural Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] The methyl ester sulfonate surfactant extracted from palm oil has also been proven to have good thermal stability and can withstand brine containing Ca 2+ and Mg 2+ . 26 N-lauroyl-L-lysine extracted from lysine, with a critical micelle concentration (CMC) of 0.4, can alter rock wettability in high salinity brine, reduce IFT by more than 40%, and has a recovery factor of about 29.61%. 27,28 Alkyl polyglucoside sodium hydroxypropyl sulfonate extracted from glucoside is effective in combination with cationic surfactant for application in low-permeability reservoirs and can maintain ultra-low IFT and low CMC.…”
Section: Introductionmentioning
confidence: 99%